Rural Finance Policies 8 - Informal markets: what lessons can we learn from them? - Sharma, Manohar; Zeller, Manfred (International Food Policy Research Institute, 2000)
In most developing countries, it is the private, informal markets that the rural poor have traditionally turned to service their financial needs. Why have these institutions succeeded in providing services to the poor when formal institutions have not? Do these informal institutions provide any lessons that bigger formal institutions could use? What are their basic limitations? Answers to such questions indicate important direc-tions for public policy.